Study of Serum Vitamin D Status in Type 2 Diabetic Patients in a Tertiary Care Hospital of Chattogram (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Hypovitaminosis D and Type 2 Diabetes Mellitus (T2DM) are public health concerns that have contributed to multiple adverse health outcomes. Recent studies linked Vitamin D Deficiency (VDD) and Insufficiency (VDI) with glycaemic control and diabetic complications in T2DM. The study assessed the association between vitamin D measured as serum 25hydroxy vitamin D [25(OH)D] level and T2DM at a tertiary care hospital in Chattogram, Bangladesh. Materials and methods: Sixty diagnosed T2DM patients (Case) attending Chittagong Medical College Hospital (CMCH) and 60 non-diabetics, apparently healthy individuals (Controls) were included in this study. Serum vitamin D levels were measured by chemiluminescent immunoassay and were categorized as Vitamin D Sufficiency (VDS) VDI and VDD with levels of  ³ 30.0, 20.0–29.9 and